Evaluation of the Usefulness of the CSR Program of Oil and Gas Companies in East Kalimantan on the Implementation of Accuracy, Suitability, and Usefulness - Sukapti Sukapti; Arie Wahyu Prananta; Agustinus Gergorius Raja Dasion (Postgraduate, University of Mataram, 2023)
The motivation to carry out activities after receiving assistance from the CSR program used as a measure in this research is to see the extent to which students' attitudes towards work behavior are based on Islamic values. The use of measuring instruments in several cultures requires an implementation process to obtain valid and reliable measuring instruments. This implementation process uses ITC references. This research aims to implement the Indonesian Santri version of an entrepreneurial intention measurement tool. Content validity uses the Content Validity Index (CVI) method, while construct validity uses the Confirmatory Factor Analysis method using Amos 23. The scale validation subjects involved 308 respondents. The results of the research show that 16 items measure motivation to carry out activities after receiving assistance from the students' CSR program. The modification results show that the model fits with 16 statements containing the Motivation factor for carrying out activities after receiving CSR program assistance, which is indicated by the Chi-Square values which are not significant, GFI (0.99), CFI (0.915), TLI (0.90) and RMSEA (0.01), This proves that the Motivation scale for carrying out activities after receiving CSR program assistance is suitable and meets the assumption of unidimensionality, and has a positive relationship with entrepreneurial motivation